Collaboration, сompliance and tax intermediaries: the case of banks. - Nurbekova, G.T.; Greggi, M. (Bulletin of the Karaganda University “Law Series”, 2023)
The purpose of the study is to assess the role of second-tier banks in the system of financial and tax intermediation, to identify the relationship between legal regulation and the actual state of cooperation between tax authorities and commercial banks, compliance with laws and regulations in the field of compliance, as well as compliance with appropriate standards of conduct, both for banks and tax authorities bodies. Features of the interaction between banks and tax authorities are the implementation of mandatory instructions and the provision of the necessary information by banks for state revenue authorities. Cooperation and interaction of the tax authorities with banks is established in the Tax Code of the Republic of Kazakhstan. The current tax and banking legislation does not adequately define the status of banks in tax administration. The Tax Code of the Republic of Kazakhstan in general terms defines the rules for cooperation and interaction between second-tier banks and tax authorities, but banking legislation in this regard bypasses this issue. In scientific terms, approaches to disclosing the essence of financial intermediation of banks are ambiguous. Cooperation in the field of taxation, objectively established in the course of the historical development of the tax system, finds its legal consolidation and design, which is studied in this scientific work. In this regard, the article defines the legal status of banks in legal relations with the tax authorities, the role of banks as financial intermediaries in tax relations. This study also carried out a general analysis of potential and actual participants in tax legal relations, the list of which does not include banks. The research methodology was composed of analytical, systematic, formal-legal methods. The theoretical basis was the works of scientists on financial, tax and banking law. The conclusions made in the course of this study can be used in further research in these areas of law, as well as for the purposes of improving tax intermediation in the current legislation of the Republic of Kazakhstan.